Determination Of Naltrexone Dosage For Narcotic Agonist Blockade In Detoxified Asian Addicts. - Jamaludin, Ailene; Mohamad, Musa; Navaratnam, Profesor Madya (Dr.) V.; Raman, N. (Pusat Penyelidikan Dadah dan Ubat-Ubatan Universiti Sains Malaysia, 1988)

(untitled)
The demand for rehabilitation of drug dependents outstrips the capacity of the Malaysian Government's rehabilitation programme and the use of opiate antagonist like Naltrexone may offer another solution to existing treatment. The objective of the above study was. to verify whether the currently American approved dose of naltrexone provided a safe and effective blockade of narcotic effects in an adult,• Malaysian population especially since the drug pattern of narcotic use and ethnic groups are different between the American and Malaysian populations.